Intangible Resources and Organizational Performance of Higher Education Institutions: A Multigroup Analysis in Gandaki Province - Chalise, Mahananda; Poudel, Birendra (The International Research Journal of Management Science, 2025)
Purpose: The study examines impact of intangible resources, organizational learning and knowledge management, on organizational performance of HEIs with mediation and multi-group analysis in Gandaki Province, Nepal. Methodology: Descriptive and causal-comparative design were used with proportionate stratified sampling of 487 staffs of constituent and affiliated campuses. PLS-SEM and PLSMGA were conducted for hypothesis testing using SmartPls version 4. Findings: Results corroborate that KM has a significant positive effect on OP, with OL playing a partial mediating role. While affiliated campuses exhibited stronger direct KM–OP links, constituent campuses relied more on OL to translate KM into performance. Multi-group analysis did not reveal any statistically significant differences among campuses. Implications: HEIs must strengthen digital KM systems, foster continuous learning cultures, and apply governance-specific measures to maximize performance. Future studies can employ longitudinal or mixed-method designs including leadership style, autonomy, and technology adaptation variables.